Diseño de un geo polímero utilizando como material precursor piedra pómez de las provincias de Cotopaxi, Imbabura y Tungurahua - Oñate Miranda, John Bryan (2022)
ABSTRACT: The construction industry is one of the sectors that produces the most pollution every year, for each ton of traditional Portland cement made, one ton of CO2 is released into the environment, this research work focuses on identifying a material that can substitute traditional Portland cement by creating a geopolymer using pumice stone from the deposits of Cotopaxi, Imbabura and Tungurahua as a precursor material, for this purpose, the chemical composition of the pumice was determined by laboratory tests. Subsequently, the alkaline activation of the geopolymer was performed with the use of NaOH and Na2SiO3 identified as alkaline activators, in 5 cm of edge cube tested to identify its compressive strength and performing an analysis of the data obtained, it was possible to identify that pumice has the characteristics and compressive strength to be considered a precursor material for geo polymers. With the results obtained from the alkaline activation, we proceeded to incorporate aggregates for the creation of geopolymer concrete by elaborating cylinders of 7.5 cm in diameter by 15 cm high and tested to identify their compressive strength. As soon as the results of the data obtained from the alkaline activation was tabulated by means of a statistical analysis and a multi-criteria analysis was carried out with the aim of consulting experts in the field in order to determine which of the three deposits studied was the best with respect to the variables chosen, being: Compressive strength, curing temperature, NaOH/Na2SiO3 ratio, NaOH molar concentration, workability and porosity. Finally, an analysis was made by the researchers with the results and the experiences gained. Keywords: Alkali-activated cement, geopolymer, pumice stone, compressive strength, geopolymer concrete.